Incorporating management flexibility: a Real Options Approach to harvesting Eucalyptus plantations - Munis, R. A. [UNESP] (2022)
The decision to harvest planted forests transcends the adopted silvicultural schedule, given that external market factors such as fluctuations in demand for timber products intensify managerial responses regarding the supply of raw materials. Therefore, forest managers need prior planning to correctly model market uncertainties and risks and thus remain nimble in decision-making. We identify the best probability distribution for modelling the price of Eucalyptus wood to assist managerial decision-making when advanced- or postponed-harvesting options are available for planted forests. Our study was based on a planted forest of Eucalyptus in an area of 11 677 ha belonging to a forest-based company in the Midwest region of the state of São Paulo, Brazil. We tested harvesting in the sixth, seventh and eighth year under the single-rotation silvicultural management system of forest reform. Our decisions are based on econometric tests and incorporate flexibility through the Real Options Approach with the Monte Carlo simulation method. The modelling of the recommended wood price was performed using fractional Brownian motion, which resulted in an expanded present value of USD 40 747 966–that is, an increase of 161% over the static present value, with a 62.7% probability of the harvest occurring in the seventh year. Thus, we conclude that the incorporation of managerial flexibility in decisions on the timing of planted-forest harvesting adds value to forest investment projects considered economically unfeasible by traditional methodologies.